Analysis of translation strategies in the Macedonian dubbing of the anime “Dragon Ball” - Ceran, Lech (Mundus Slavicus I, 2025)
“Dragon Ball” by Akira Toriyama is currently a global phenomenon. It is not only considered one of the Japanese comics and animation classics, but for many people it was also the first contact with Japanese culture. Undoubtedly, one of the merits of the series’ popularity is its localization into different languages – with the anime adaption playing the main role. It was no different in the case of North Macedonia, where the anime series were dubbed. The article is a compilation of information about this language version, with focus on brief analysis of translation strategies.